Hepatectomy for hepatocellular carcinoma larger than 10 cm: preoperative risk stratification to prevent futile surgery. Issue 7 (July 2015) - Lim, Chetana; Compagnon, Philippe; Sebagh, Mylène; Salloum, Chady; Calderaro, Julien; Luciani, Alain; Pascal, Gérard; Laurent, Alexis; Levesque, Eric; Maggi, Umberto; Feray, Cyrille; Cherqui, Daniel; et al.
Abstract: Objectives: Appropriate patient selection is important to achieving good outcomes and obviating futile surgery in patients with huge (≥10 cm) hepatocellular carcinoma (HCC). The aim of this study was to identify independent predictors of futile outcomes, defined as death within 3 months of surgery or within 1 year from early recurrence following hepatectomy for huge HCC. Methods: The outcomes of 149 patients with huge HCCs who underwent resection during 1995–2012 were analysed. Multivariate logistic regression analysis was performed to identify preoperative independent predictors of futility. Results: Independent predictors of 3‐month mortality (18.1%) were: total bilirubin level >34 μmol/l [ P = 0.0443; odds ratio (OR) 16.470]; platelet count of <150 000 cells/ml ( P  = 0.0098; OR 5.039), and the presence of portal vein tumour thrombosis ( P  = 0.0041; OR 5.138). The last of these was the sole independent predictor of 1‐year recurrence‐related mortality (17.2%). Rates of recurrence‐related mortality at 3 months and 1 year were, respectively, 6.3% and 7.1% in patients with Barcelona Clinic Liver Cancer (BCLC) stage A disease, 12.5% and 14% in patients with BCLC stage B disease, and 37.8% ( P = 0.0002) and 75% ( P = 0.0002) in patients with BCLC stage C disease. Conclusions: According to the present data, among patients submitted to hepatectomy for huge HCC, those with a high bilirubin level, low platelet count and portal vein thrombosis are at higher risk for futile surgery. The presence of portal vein tumour thrombosis should be regarded as a relative contraindication to surgery.